Neuropathology of dementia in patients with Parkinson's disease: a systematic review of autopsy studies. Issue 11 (23rd August 2019) - Smith, Callum; Malek, Naveed; Grosset, Katherine; Cullen, Breda; Gentleman, Steve; Grosset, Donald G
Abstract : Background: Dementia is a common, debilitating feature of late Parkinson's disease (PD). PD dementia (PDD) is associated with α-synuclein propagation, but coexistent Alzheimer's disease (AD) pathology may coexist. Other pathologies (cerebrovascular, transactive response DNA-binding protein 43 (TDP-43)) may also influence cognition. We aimed to describe the neuropathology underlying dementia in PD. Methods: Systematic review of autopsy studies published in English involving PD cases with dementia. Comparison groups included PD without dementia, AD, dementia with Lewy bodies (DLB) and healthy controls. Results: 44 reports involving 2002 cases, 57.2% with dementia, met inclusion criteria. While limbic and neocortical α-synuclein pathology had the strongest association with dementia, between a fifth and a third of all PD cases in the largest studies had comorbid AD. In PD cases with dementia, tau pathology was moderate or severe in around a third, and amyloid-β pathology was moderate or severe in over half. Amyloid-β was associated with a more rapid cognitive decline and earlier mortality, and in the striatum, distinguished PDD from DLB. Positive correlations between multiple measures of α-synuclein, tau and amyloid-β were found. Cerebrovascular and TDP-43 pathologies did not generally contribute to dementia in PD. TDP-43 and amyloid angiopathy correlated with coexistent Alzheimer pathology. Conclusions: While significant α-synuclein pathology is the main substrate of dementia in PD, coexistent pathologies are common. In particular, tau and amyloid-β pathologies independently contribute to the development and pattern of cognitive decline in PD. Their presence should be assessed in future clinical trials where dementia is a key outcome measure. Trial registration number: CRD42018088691 .